Microwave-Assisted Metathetic Synthesis of Ag-MWO4/Zeolite-A (M = Co, Ni) Porous Composites - Lim, C.S. (Asian Journal of Chemistry, 2011)
Ag-MWO4/zeolite-A (M = Co, Ni) porous composites were synthesized using a solid-state metathetic (SSM) method with microwave irradiation. The characteristics of the solid-state metathetic reaction and the formation of the high lattice energy by-product NaCl were found to drive the reaction for wolframite-type CoWO4 and NiWO4 toward completion. The Ag-MWO4/zeolite-A (M = Co, Ni) porous composites were formed completely at 600 ºC. Monoclinic-like crystals of CoWO4 and NiWO4 were primarily co-mixed with porous zeolite-A. Small spherical silver particles were immobilized in the porous MWO4/zeolite-A (M = Co, Ni) matrix.